What is a social determinant of health? Back to basics - Robert A. Hahn (SAGE Publishing, 2021)
The objective of this essay is to clarify the understanding and use of Social Determinants of Health by exploring basic characteristics of 'determinants' and 'fundamental causes,' the 'social,' 'structure,' and 'modifiability,' and to consider theoretical and practical implications of this reconceptualization for public health.  The analysis distinguishes SDOH from other determinants of health. Social determinants of health are defined as mutable societal systems, their components, and the social resources and hazards for health that societal systems control and distribute, allocate and withhold, and that, in turn, cause health consequences, including changes in the demographic distributions and trends of health.  A systems conceptualization holds concepts such as "race" as the creations of social systems and as having negative consequences, such as racism, when part of a racist system, but potentially ameliorative consequences when part of an anti-racist system. The integration of SDOH into public health theory and practice may substantially expand the benefits of public health, but will require new theorizing, intervention research, education, collaboration, policy, and practice.